2010
DOI: 10.1007/s00424-010-0807-3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in diabetes: multiple targets for treatment

Abstract: Robert Furchgott's discovery of the obligatory role that the endothelium plays in the regulation of vascular tone has proved to be a major advance in terms of our understanding of the cellular basis of diabetic vascular disease. Endothelial dysfunction, as defined by a reduction in the vasodilatation response to an endothelium-dependent vasodilator (such as acetylcholine) or to flow-mediated vasodilatation, is an early indicator for the development of the micro- and macroangipathy that is associated with diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 186 publications
(183 reference statements)
2
66
0
2
Order By: Relevance
“…There is experimental and clinical evidence for the presence of impaired endothelium-dependent vasodilation in various vascular beds of animal models of diabetes or in humans with type 1 and type 2 diabetes (18,20,22,27). The results of the present study clearly demonstrate the significant attenuation of ACh-induced vasodilation of small radial uteroplacental arteries from diabetic pregnant rats.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…There is experimental and clinical evidence for the presence of impaired endothelium-dependent vasodilation in various vascular beds of animal models of diabetes or in humans with type 1 and type 2 diabetes (18,20,22,27). The results of the present study clearly demonstrate the significant attenuation of ACh-induced vasodilation of small radial uteroplacental arteries from diabetic pregnant rats.…”
Section: Discussionsupporting
confidence: 63%
“…The colocalization of the endothelial ER and IK Ca channels in myoendothelial projections of the mesenteric vasculature has been recently reported (48 Hyperglycemia is considered as a major causal factor of diabetes-associated endothelial dysfunction in animals and humans (20,22,30,31). However, experimental studies of hyperglycemia-evoked vascular effects have produced conflicting results.…”
Section: H942mentioning
confidence: 99%
See 1 more Smart Citation
“…31 The generation of NO is regulated by both the absolute level of eNOS protein and protein kinase B (Akt)-mediated phosphorylation of the eNOS level. 32 As mentioned earlier, the activation of PKC β isoforms inhibits phosphorylation of eNOS via a PI3K/Akt pathway that is stimulated by insulin. Furthermore, VEGF itself has effects on the phosphorylation of eNOS through this same pathway.…”
mentioning
confidence: 88%
“…Endothelial dysfunction is considered a key mechanism of diabetic vascular disease, as evidenced by impaired endothelium-dependent vasodilation in various vascular beds of diabetic animals and humans (12)(13)(14)20). Previously, we demonstrated that EDHF-mediated uterine vasodilation was severely reduced by diabetic pregnancy, indicating that an impairment of the EDHF system importantly contributes to uteroplacental endothelial dysfunction (24).…”
Section: Discussionmentioning
confidence: 95%